BOOK REVIEW: VALUTARE L’IMPATTO DEGLI INTERVENTI SUI BENI CULTURALI ATTRAVERSO IL METODO SOPHIA. IL CASO TEATRO AKROPOLIS (EVALUATING THE IMPACT OF INTERVENTIONS ON CULTURAL HERITAGE THROUGH THE SOPHIA METHOD: THE CASE OF TEATRO AKROPOLIS), BY MICHELA MARCHIORI, MAURO BAIONI, FLAVIA MARUCCI, CHIARA PETRINI, WORKING PAPER SERIES DEPARTMENT OF BUSINESS STUDIES ROMA TRE – “BS RM3”, 2024 - Cipriano, Maria Antonietta (Piccola Impresa / Small Business, 2025)
This volume presents the first Italian application of the SoPHIA method, a holistic framework for evaluating cultural heritage interventions, tested at Teatro Akropolis in Genoa. Developed within a Horizon 2020 project, SoPHIA assesses impacts across three dimensions: domains, people, and time. The case of Teatro Akropolis, a small performing arts centre undergoing strategic transformation, illustrates how the method supports participatory evaluation, internal reflection, and future planning. Findings highlight the method’s multidimensionality, stakeholder engagement, and its capacity-building potential. The study underscores the value of flexible evaluation tools tailored to the complex realities of small cultural organizations.